(3dHGH GdETGQGJ bSe GdWHjYjGJs - (3GdJjej, GdHcQj, GdWHQSJGfj, GdQGRj, GdTGaYj, CHh YHO Gddg, GHf NWjH GdQj, aNQ GdOjf, eMeO Hf YeQ Hf GdMSf Hf GdMSjf, (B606 (3g`s
(3ChdgG (B:s
(3HYO GdHSedI ; dbO CJjfG Ydi bSe GdefWb ef TQM GdTQM ehajf Mbg ef GdJLQjf efXejf dBdjg aj SeW GdJbQjQ aLQi HfG GdBf Cf (B( ) (3aj TQM GdWHjYjGJs
(3BNQgG (B:s
(3GdJQcjH HGdJaQjb ZjQ eYbhd aEf (B( ) (3Edi GdLRFjGJ jSJMjd Cf jchf eQcHG hEdG de jcfRFjGJg (B( ) (3CLRGA hGddg CYde HGdUhGHs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B6 / 313s
(3eYLe GdeDdajf (B2 / 558s
(3cTa GdXfhf (B1/ 94s
(3TPQGJ GdPgH (B5 / 21s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdadSaI hGdefWbs